Trauma fiction - Whitehead, Anne, 1971- (Edinburgh University Press, 2004)
Displays intelligence, deep understanding of the conceptual issues surrounding trauma as a literary subject and originality. The book marks an important step forward in the development of trauma studies.' - Cathy Caruth, Winship Distinguished Professor of Comparative Literature and English, Emory University The literary potential of trauma is examined in this book, bringing trauma theory and literary texts together for the first time. Trauma Fiction focuses on the ways in which contemporary novelists explore the theme of trauma and incorporate its structures into their writing. It provides innovative readings of texts by Pat Barker, Jackie Kay, Anne Michaels, Toni Morrison, Caryl Phillips, W. G. Sebald and Binjamin Wilkomirski. It also considers the ways in which trauma has affected fictional form, exploring how novelists have responded to the challenge of writing traumatic narratives, and identifying the key stylistic features associated with the genre. In addition, the book introduces the reader to key critics in the field of trauma theory such as Cathy Caruth, Shoshana Felman and Geoffrey Hartman. The linking of trauma theory and literary texts not only sheds light on works of contemporary fiction, it also points to the inherent connections between trauma theory and the literary which have often been overlooked. The distinction between literary theme and style in the book opens up major questions regarding the nature of trauma itself. Trauma, like the novels discussed, is shown to take an uncertain but productive place between content and form. Key Features Idenitifes and explores a new and evolving genre in contemporary fiction Thinks through the relation between trauma and literature Produces innovative readings of key works of contemporary fiction Provides an introduction to key ideas in trauma theory Table of Contents Acknowledgements Part I: Theme Introduction to Part I: Theme 1. The Past as Revenant: Trauma and Haunting in Pat Barker's Another World 2. Telling Tales: Trauma and Testimony in Binjamin Wilkomirski's Fragments 3. 'Ground that will remember you': Trauma and Landscape in Anne Michaels's Fugitive Pieces Part II: Style Introduction to Part II: Style 4. Othello in the Ghetto: Trauma and Intertextuality in Caryl Phillips's The Nature of Blood 5. The Butterfly Man: Trauma and Repetition in the Writing of W. G. Sebald 6. Recomposing the Past: Trauma and Improvisation in Toni Morrison's Jazz and Jackie Kay's Trumpet Conclusion Notes Bibliography